Signal Peptide Requirements for Lymphocytic Choriomeningitis Virus Glycoprotein C Maturation and Virus Infectivity - Schrempf, Sabrina (American Society for Microbiology (ASM), 2007)
Insertion of the lymphocytic choriomeningitis virus (LCMV) precursor glycoprotein C (GP-C) into the membrane of the endoplasmic reticulum is mediated by an unusual signal peptide (SP(GP-C)). It is comprised of 58 amino acid residues and contains an extended hydrophilic N-terminal region, two hydrophobic regions, and a short C-terminal region. After cleavage by signal peptidase, SP(GP-C) accumulates in cells and virus particles. In the present study, we identified the LCMV SP(GP-C) as being an essential component of the GP complex and show that the different regions of SP(GP-C) are required for distinct steps in GP maturation and virus infectivity. More specifically, we show that one hydrophobic region of SP(GP-C) is sufficient for the membrane insertion of GP-C, while both hydrophobic regions are required for the processing and cell surface expression of the GPs. The N-terminal region of SP(GP-C), on the other hand, is essential for pseudoviral infection of target cells. Furthermore, we show that unmyristoylated SP(GP-C) exposes its N-terminal region to the exoplasmic side. This SP(GP-C) can promote GP-C maturation but is defective in pseudoviral infection. Myristoylation and topology of SP(GP-C) in the membrane may thus hold the key to an understanding of the role of SP(GP-C) in GP-C complex maturation and LCMV infectivity.